2008
DOI: 10.1371/journal.pone.0003707
|View full text |Cite
|
Sign up to set email alerts
|

p53 Plays a Role in Mesenchymal Differentiation Programs, in a Cell Fate Dependent Manner

Abstract: BackgroundThe tumor suppressor p53 is an important regulator that controls various cellular networks, including cell differentiation. Interestingly, some studies suggest that p53 facilitates cell differentiation, whereas others claim that it suppresses differentiation. Therefore, it is critical to evaluate whether this inconsistency represents an authentic differential p53 activity manifested in the various differentiation programs.Methodology/Principal FindingsTo clarify this important issue, we conducted a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
143
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 61 publications
(91 reference statements)
13
143
1
3
Order By: Relevance
“…3,4 We use our reporter system to show that basal p53 activity decreases as the ES cells differentiate and that differentiated ES cells are thus less sensitive to basal stress-induced p53 activation. Interestingly, p53 protein levels are higher in differentiating ES cells, suggesting that there is an Mdm2-and degradation-independent mechanism by which p53 activity is inhibited.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 We use our reporter system to show that basal p53 activity decreases as the ES cells differentiate and that differentiated ES cells are thus less sensitive to basal stress-induced p53 activation. Interestingly, p53 protein levels are higher in differentiating ES cells, suggesting that there is an Mdm2-and degradation-independent mechanism by which p53 activity is inhibited.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The transcription factor p53 has been shown to play a role in differentiation. 3,4 It is also crucial for the regulation of cell proliferation and for the maintenance of genomic integrity, which is essential in these ES cells in order to prevent tumorigenesis. Therefore, we sought to examine p53 activity and regulation in differentiating ES cells.…”
Section: Introductionmentioning
confidence: 99%
“…18 This multitask protein may either induce or suppress key differentiation factors depending on the specific cellular fate. 19 Although increasing evidence from in vitro and in vivo studies suggest that p53 exerts a negative effect on white adipogenic differentiation, 19,20,21 its role in brown fat differentiation has not been determined.…”
mentioning
confidence: 99%
“…Our previous study demonstrated a negative regulatory role of p53 in white adipogenic differentiation of mouse embryonic fibroblasts (MEFs). 19 To corroborate the negative effect that p53 exerts on white adipogenic differentiation, we used additional mouse and human cell lines that represent various stages of adipogenic differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation